Preliminary Evidence on Pulmonary Function after Asymptomatic and Mild COVID-19 in Children - Costanza Di Chiara; Silvia Carraro; Stefania Zanconato; Sandra Cozzani; Eugenio Baraldi; Carlo Giaquinto; Valentina Agnese Ferraro; Daniele Donà (MDPI AG, 2022)
Background: While it has been described that adults can develop long-lasting deterioration in pulmonary function (PF) after coronavirus disease 19 (COVID-19), regardless of disease severity, data on the long-term pneumological impact of SARS-CoV-2 infection in children are lacking. Methods: Performing a single-center, prospective, observational study on children aged 6-18 years with a previous diagnosis of asymptomatic/mild COVID-19, we evaluated the long-term impact of mild severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children. Results: A total of 61 subjects underwent spirometry after a mean time of 10 ± 4 months from asymptomatic or mild infection. None of the children reported any respiratory symptoms, needed any inhaled therapy, or had abnormal lung function. Conclusions: In our study, we observed that children and adolescents did not develop chronic respiratory symptoms and did not present lung function impairment after asymptomatic or mild SARS-CoV-2 infection.